The Black American short story in the 20th century : a collection of critical essays - Bruck, Peter (Grüner, 1977)
This volume is a collection of essays on black short stories written between 1998 and 1976. It aims to say something about the black short story as a genre and the development of the racial situation in America as well. The primary aim is to introduce the reader to this long neglected genre of black fiction. In contrast to the black novel, the short story has hardly been given extensive criticism, let alone serious attention. The individual essays of this collection aim at presenting new points of critical orientation in the hope of reviving and fostering further discussions. They provide a va.
Keywords: Short stories, American -- History and criticism.; American fiction -- African American authors -- History and criticism.; American fiction -- 20th century -- History and criticism.; African Americans -- Intellectual life -- 20th century.; African Americans in literature.; Nouvelles américaines -- Auteurs négro-américains -- Histoire et critique.; Nouvelles américaines -- Histoire et critique.; Roman américain -- Auteurs noirs américains -- Histoire et critique.; Roman américain -- 20e siècle -- Histoire et critique.; Noirs américains -- Vie intellectuelle -- 20e siècle.; Noirs américains dans la littérature.; LITERARY CRITICISM -- American -- General.; African Americans in literature; African Americans -- Intellectual life; American fiction; American fiction -- African American authors; Short stories, American; Kurzgeschichte; Aufsatzsammlung; USA; Schwärze; 1900-1999; Aufsatzsammlung.; Criticism, interpretation, etc.